2020
DOI: 10.1111/apt.15899
|View full text |Cite
|
Sign up to set email alerts
|

Letter: is unrealised adult height resulting from paediatric Crohn’s disease associated with a potential reduction in lifetime earnings? Authors’ reply

Abstract: LINKED CONTENT This article is linked to Mouratidou et al and Hron papers. To view these articles, visit https://doi.org/10.1111/apt.15667 and https://doi.org/10.1111/apt.15828.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…6 Early use of biologics is another effective strategy to promote mucosal healing, increasing both linear growth and height velocity, with the most profound effects in pre-pubertal children. 7 Our…”
Section: Letter: Is Unrealised Adult Height Resulting From Paediatricmentioning
confidence: 96%
See 1 more Smart Citation
“…6 Early use of biologics is another effective strategy to promote mucosal healing, increasing both linear growth and height velocity, with the most profound effects in pre-pubertal children. 7 Our…”
Section: Letter: Is Unrealised Adult Height Resulting From Paediatricmentioning
confidence: 96%
“…3 To what extent this difference also results in future lost life chances (eg not as good educational results and less well-paid employments as would have been expected) and reduction in lifetime earnings is yet to be shown. More importantly, many studies have also shown that patients with IBD, regardless of age of diagnosis, have more work loss (sick leave and disability pension) than matched reference individuals or IBD-free siblings [4][5][6][7][8][9] ; these observations to us suggests that it is the disease itself, with its remitting and relapsing disease course, rather than the (limited) reduction in adult height that causes reduced lifetime earnings. That is, if lifetime earnings are indeed reduced, which is yet to be shown (although we agree it is likely).…”
Section: Hron Et Al Cite Papers Correlating Height With Lifetime Earningmentioning
confidence: 99%